Deterioration of autoimmune condition associated with repeated injection of dextranomer/hyaluronic acid copolymer: A case report - Kazuto Suda; Toshihiro Yanai; Hajime Kawakami; Takato Sasaki; Miki Ishikawa; Miki Toma; Toshihiro Muraji (Elsevier, 2016)
A 6-year-old girl underwent ureterocystoneostomy (UCN) because of left flank pain due to delayed onset of ureteral stenosis one and a half years after endoscopic dextranomer/hyaluronic acid copolymer (Deflux) injection for the treatment of vesicoureteral reflux (VUR). Histopathological examination indicated chronic inflammation with abundant eosinophils characteristic of a reaction to Deflux. Several autoimmune diseases developed during the treatment for ureteral stenosis. First, 2 weeks prior to the onset of left flank pain, she was diagnosed as having systemic lupus erythematosus. Finally, she died of pulmonary hemorrhage due to thrombotic thrombocytopenic purpura 4 months after UCN. The fatal outcome in this case was suspected to be caused by autoimmune syndrome induced by adjuvants, which in this case was the hyaluronic acid polymer injected into the ureteric orifice for the treatment of VUR.